Prevalence of Birth Defects and Associated Risk factors among Neonates in Tertiary Care Hospital, Shivamogga, Karnataka - P Vijayalakshmi; B Chandrashekar; NP Navya; GM Manoj (JCDR Research and Publications Pvt. Ltd., 2021)
Introduction: Birth Defects (BD) account for a significant proportion of neonatal mortality. BD can result in long-term disability with a significant impact on individuals, families, societies and healthcare systems. Aim: To estimate prevalence, types, clinical profile and perinatal profile of BD among neonates. Materials and Methods: This was a prospective observational study conducted in the Neonatal Intensive Care Unit (NICU), Department of Paediatrics, from November 2018 to May 2019. A total of 71 cases were admitted to NICU with BD. All the demographic details, natal ,ante-natal, pre-natal clinical data and family histories were collected with the help of a predesigned proforma, entered in excel sheet and analysed using Statistical Package for Social Sciences (SPSS) software; version 25.0. The p-value was calculated using chisquare test and p-value < 0.05 was taken as significant. Results: Total number of neonates with BD was 71 (4.16% of total NICU admissions, 1.18% of total live births i.e., 6033). Neonates with single BD were 53 (74.65%) and multiple BDs were 18 (25.35%). Mean age was 3.89±5.29 days. Out of the 71 neonates, 37(52.11%) were males while 28 (39.44%) were females, and the rest 6 (8.45%) had ambiguous genitalia. Prevalence of BD was more in Low Birth Weight (LBW) (6.27%, 34/542 cases) than normal birth weight babies (3.33%, 36/1080 babies). Prevalence of BD was highest in mothers of 26-30 years age group (28/433, 6.46%). The predominant system involved was cardiovascular system (29 out of total of 95 BDs, 30.53%). The most common major BD was Ventricular Septal Defect (VSD) (13 out of 95 BDs, 13.68%). The predominant type of BD found was malformation (83 out of 95 BDs, 87.37%). Case fatality rate of BDs was 30.99% (22/71). Neonatal mortality rate of BDs was 0.35 per 1000 live births. Conclusion: Prevalence of birth defects was 1.18% of the total live births. Cardiovascular system was the most common system involved, VSD being the most common defect. BDs were significantly associated with late twenties parity, LBW and pre-existing medical diseases in mothers. Single and major BDs were more common than their counterparts.